On Some Predictive Ratio Type Estimators in Two Stage Sampling - A.K.P.C. Swain; Sitanshu Shekhar Mishra; B.K. Pradhan (Journal of Statistical Theory and Applications (JSTA), 2013)
Some predictive ratio type estimators in two stage sampling are derived following the model free predictive criterion proposed by Basu (1971) and these estimators are compared with the classical multistage ratio estimator and also with Smith’s (1969) multistage ratio estimator. A numerical illustration is provided to compare the efficiencies of different predictive estimators.